The Effectiveness of Using Google Sites-Based E-Modules to Optimize Critical Thinking Skills: Student Perceptions Analysis - Ernita Susanti; Sandi Septiana; Shofa Meilinda; Intannia Mulya Rosa (Postgraduate, University of Mataram, 2023)
21st century learning emphasizes the importance of students' critical thinking skills and mastery of information technology. One use of technology in the learning process is through interactive learning media such as e-modules. Using e-modules can facilitate the development of critical thinking skills in students. One platform that can be used to create e-modules is Google Sites. This research aims to determine student perceptions of the effectiveness of Google Sites-based e-modules to facilitate students' critical thinking skills. This research uses a quantitative descriptive approach, with data collection techniques using a Likert scale questionnaire. The analysis results show that the assessment of the usefulness or students' perception of the e-module reached 85.48, including the very high sort. Apart from that, the analysis regarding the influence of e-modules on changes in knowledge and skills earned a score of 81.45, including the high kind. Based on the analysis of student perceptions, a positive response was found towards using e-modules, which indicates that the e-modules used are effective. Therefore, e-modules can be an effective learning medium in increasing understanding and facilitating students' critical thinking skills.